Fuzzy-set qualitative comparative analysis of influencing factors on family doctor service performance during major public health emergencies - Gan Wang; Gan Wang; Li Luo; Li Luo (Frontiers in Public Health)
ObjectiveBy studying the Technology-Organization-Environment Framework (TOE), this research explores the impact of various indicators in technology, organization, and environment on the performance of family doctor services during major public health emergencies. It aims to identify the driving paths to improve performance.MethodsA stratified sampling of 34 community health service centers in Shanghai was conducted, using the comprehensive performance score of family doctors as the outcome variable. The Average Internet Medical Service Person-times and the Information Technology Expenditure per Thousand Population were considered as technology-related variables. The Fiscal Allocation per Thousand Population (/1,000), the Family Doctor Team Members per Thousand Population, and the Medical Social Workers and Volunteers per Thousand Population were identified as organization-related variables. The Proportion of Older Adult Population, Fiscal Allocation per Thousand Population, and the number of patient self-education organizations per thousand population were taken as environment-related variables. Fuzzy-set Qualitative Comparative Analysis (fsQCA) was employed to conduct necessity analysis, truth table analysis, and configurational analysis of antecedent conditions, with robustness tests performed by adjusting consistency thresholds and case frequencies.ResultsThe study found that the performance of family doctor services was influenced by multiple factors, with no single decisive factor. In overall communities, five configurations, including per capita fiscal allocation and community participation, affected performance, explaining 4.2% of the variance. In central urban areas, information technology expenditure and the Proportion of Older Adult Population were core conditions, influencing 27.5% of performance paths. In non-central urban areas, core conditions such as financial support and IT covered 53.9% of data cases. The fsQCA results, which were robustly tested, begin to provide a strong basis for resource allocation and policy formulation.ConclusionThis study begins to fill the gap in research on family doctor service performance during major public health emergencies, exploring the synergistic effects and causal asymmetry among multiple indicators such as technology, organization, and environment from a holistic, or configurational, perspective.